A new, easy-to-make pectin-honey hydrogel enhances wound healing in rats - Gessica Giusto; Cristina Vercelli; Francesco Comino; Vittorio Caramello; Massimiliano Tursi; Marco Gandini (BMC, 2017)
Abstract Background Honey, alone or in combination, has been used for wound healing since ancient times and has reemerged as a topic of interest in the last decade. Pectin has recently been investigated for its use in various biomedical applications such as drug delivery, skin protection, and scaffolding for cells. The aim of the present study was to develop and evaluate a pectin-honey hydrogel (PHH) as a wound healing membrane and to compare this dressing to liquid honey. Methods Thirty-six adult male Sprague-Dawley rats were anesthetized and a 2 × 2 cm excisional wound was created on the dorsum. Animals were randomly assigned to four groups (PHH, LH, Pec, and C): in the PHH group, the pectin-honey hydrogel was applied under a bandage on the wound; in the LH group, liquid Manuka honey was applied; in the Pec group, pectin hydrogel was applied (Pec); and in the C group, only bandage was applied to the wound. Images of the wound were taken at defined time points, and the wound area reduction rate was calculated and compared between groups. Results The wound area reduction rate was faster in the PHH, LH, and Pec groups compared to the control group and was significantly faster in the PHH group. Surprisingly, the Pec group exhibited faster wound healing than the LH group, but this effect was not statistically significant. Conclusion This is the first study using pectin in combination with honey to produce biomedical hydrogels for wound treatment. The results indicate that the use of PHH is effective for promoting and accelerating wound healing.